Beyond the normal breast anatomy: A case of benign bilateral accessory breasts - Joshua Lewis; Chiedza Mutindori; Blancheneige Beohon; Bryce Gantt; Nia Hammett; Akeem Henry; Alexis Kitchens; Calah Burros; Oyetokunbo Ibidapo-Obe (SAGE Open Medical Case Reports)
Accessory breast tissue, or polymastia, is a rare developmental anomaly resulting from incomplete regression of the embryonic mammary ridge. While often asymptomatic, accessory breast tissue can respond to hormonal fluctuations, leading to pain, swelling, or lactation. We present the case of a 39-year-old woman with bilateral axillary accessory breast tissue and accessory nipples, who reported cyclical pain and lactation from the accessory tissue during nursing. Her symptoms, exacerbated during menstruation, significantly impacted her quality of life. Diagnostic imaging confirmed benign glandular tissue, and surgical excision was performed for symptom relief. Histopathological analysis revealed no malignancy. This case highlights the clinical importance of recognizing accessory breast tissue as a potential source of cyclical axillary symptoms and underscores the need for timely diagnosis and tailored surgical management.